2011
DOI: 10.1021/ma2016387
|View full text |Cite
|
Sign up to set email alerts
|

Well-Defined Poly(lactic acid)s Containing Poly(ethylene glycol) Side Chains

Abstract: Poly(ethylene glycol) (PEG) side-chain functionalized lactide analogues have been synthesized in four steps from commercially available L-lactide. The key step in the synthesis is the 1,3-dipolar cycloaddition between PEG-azides and a highly strained spirolactide-heptene monomer, which proceeds in high conversions. The PEG-grafted lactides analogues were polymerized via ring-opening polymerization using triazacyclodecene as organocatalyst to give well-defined tri- and hepta-(ethylene glycol)-poly(lactide)s (PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 30 publications
0
68
0
Order By: Relevance
“…This sequence was first reported by Hillmyer et al in 2008, and it proceeded as described in the literature. 46-48 …”
Section: Resultsmentioning
confidence: 99%
“…This sequence was first reported by Hillmyer et al in 2008, and it proceeded as described in the literature. 46-48 …”
Section: Resultsmentioning
confidence: 99%
“…The water for spectra determination was deionized water without fluorescent impurities. Compounds 1 [15] and 3 [16] were prepared as described. All other solvents and reagents were of reagent grade and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of 1-(tert-butyloxycarbonyl)-ethyldiamine (1) [15] with propargyl bromide in the presence of K 2 CO 3 in dichloromethane afforded alkyne 2 in 90% yield. This compound then underwent a typical click reaction with azide 3, [16] which was prepared as described, in the presence of CuSO 4 •5H 2 O and sodium ascorbate to give 4 in 96% yield. Deprotection of this compound with trifluoroacetic acid (TFA) in dichloromethane produced amine 5, which was condensed with perylene-3,4:9,10-tetracarboxylic dianhydride using imidazole as a base to give probe 6 in 31% yield.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…MLA was first synthesized in 1969 by Scheibelhoffer et al through a bromination of L-lactide followed by a basic HBr elimination [2]. In 2008, the first Diels–Alder reaction employing MLA as dienophile was described [36]. In a recent NMR study we demonstrated that, poly(MLA) prepared via free radical polymerization contains mainly isotactic units.…”
Section: Introductionmentioning
confidence: 99%